2012
DOI: 10.1177/000313481207800825
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis between Laparoscopic and Open Ventral Hernia Repair at a Tertiary Care Center

Abstract: Laparoscopic ventral hernia repair reportedly yields lower postoperative complications than open repair. We hypothesized that patients undergoing laparoscopic repair would have lower postoperative infectious outcomes. Also, certain preoperative patient characteristics and preoperative hernia characteristics are hypothesized to increase complication risk in both groups. All ventral hernia repairs performed at University of Virginia from January 2004 to January 2006 were reviewed. Primary outcomes included wound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 12 publications
5
7
0
Order By: Relevance
“…Consistent with prior studies,[ 2 4 5 6 ] there was a significant decrease in surgical site infection rates when comparing laparoscopic to open VHR, as well as robotic, assisted to open VHR (OR lap vs. open 0.44 [0.29–0.66] and OR robot vs. open 0.30 [0.08–0.81]). However, there was no difference in surgical site infection rates when comparing laparoscopic and robotic-assisted VHR head-to-head (OR robot vs. lap 0.68 [0.19–1.80]).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Consistent with prior studies,[ 2 4 5 6 ] there was a significant decrease in surgical site infection rates when comparing laparoscopic to open VHR, as well as robotic, assisted to open VHR (OR lap vs. open 0.44 [0.29–0.66] and OR robot vs. open 0.30 [0.08–0.81]). However, there was no difference in surgical site infection rates when comparing laparoscopic and robotic-assisted VHR head-to-head (OR robot vs. lap 0.68 [0.19–1.80]).…”
Section: Resultssupporting
confidence: 87%
“…Ventral hernia repair (VHR) is one of the most commonly performed general surgery procedures in the United States. [ 1 2 ] Since the first laparoscopic VHR in the early 1990s,[ 3 ] multiple studies have shown the advantages of laparoscopic over open VHR, particularly decreased hospital length of stay and lower instances of surgical site infections. [ 2 4 5 6 ] However, studies have also shown increased rates of serious complications with laparoscopic VHR such as enterotomy, especially in cases with significant lysis of adhesions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DM patients carry a higher risk of SSI in open and laparoscopic hernia repairs. 11 Infection is a risk factor for the development of incisional hernia, so having DM should increase the risk of recurrence. However, in our series, DM patients who had a recurrence did not have documented evidence of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic approach to uncomplicated ventral hernia repair as compared to open repair has advantages of less post-operative pain, reduced risk of wound infection,[ 1 2 ] early recovery, short hospital stay and decreased overall cost of treatment. [ 3 4 5 ] Patient satisfaction after laparoscopic procedure is also better as compared to open repair.…”
Section: Introductionmentioning
confidence: 99%